Improving the Ability of Class VII Students in Writing Procedure Texts Through Local Culture-Based Learning - Arianto Arianto (Persatuan Guru Republik Indonesia Provinsi sulawesi Tenggara, 2022)
This study aimed to improve the ability of class VII students to write procedural texts through learning based on local culture. Local culture-based learning is a strategy for creating a learning environment and designing learning experiences that integrate culture as part of the learning process. The method used in this paper is classroom action research (CAR). The type of research is qualitative research, designed with classroom action research design carried out in cycles. The research subjects were students of class VII-A, with 33 students consisting of 22 boys and 11 girls. Writing procedure texts through local culture-based learning can increase student activity and learning outcomes. It can be shown that the average student activity reaches 73% in the first cycle, and in the second cycle, it increases to 93%. And student learning outcomes in the first cycle with a complete learning level reached 20 students or 60.6% with an average of 75.45; in the second cycle, 33 students completed or 100% with an average of 92.88. Writing procedure texts through local culture-based learning is a strategy for integrating culture as part of the learning process.